One-visit preformed space maintainer: A case report - Setyowati, Erika; Nelwan, Sindy Cornelia; Ramakrishnan, Krishna Kumar (Indonesian Journal of Dental Medicine, 2025)
Background: In paediatric dentistry, space maintainer is crucial for maintaining arch length after early tooth loss. Dental arch development can be greatly impacted by the early loss of primary teeth, particularly posterior teeth like primary molars. Adjacent teeth may drift, the midline may deviate, the length of the arch may shorten, and the emergence of permanent successors may be disrupted. Purpose: The goal of this case study is to demonstrate how well a prefabricated space maintainer works for a young child who needs few dental appointments. Case: The lower right primary first molar of a 5-year-old kid had significant caries. With neighbouring teeth intact and no indications of infection or systemic anomalies, a clinical and radiographic evaluation confirmed the need for extraction. Case Management: Tooth #84 was extracted under local anaesthesia the same day, and a prefabricated band and loop space maintainer was chosen. Without the need for laboratory procedures, the appliance was modified chairside and cemented in a single visit. For the underlying permanent successor, it offered appropriate space maintenance. To evaluate oral hygiene and appliance stability, the patient was scheduled for routine follow-ups. This case demonstrates the clinical advantage of utilising a premade band and loop space maintainer in a single-visit procedure after a young child's non-restorable primary molars were extracted. Conclusion: When cooperation or access to care is restricted, preformed space maintainers provide a rapid, efficient, and kid-friendly way to preserve arch integrity after early tooth loss in the primary dentition.